WAYS TO IMPROVE THE EFFICIENCY OF FINANCIAL MANAGEMENT IN COMPANIES (American Journal of Business Management, Economics and Banking, 2025)
This article explores effective ways to improve the efficiency of financial management in companies by focusing on strategic, technological, and operational dimensions. In the context of increasing market volatility and evolving stakeholder expectations, efficient financial management has become a critical determinant of corporate sustainability and competitiveness. The study analyzes key components such as cost optimization, liquidity management, investment planning, and financial risk mitigation. Special attention is given to the integration of digital financial tools and data-driven decision-making processes that enhance financial transparency, accuracy, and responsiveness. Through a review of global best practices and comparative analysis of financial performance indicators, the article identifies practical mechanisms for strengthening internal financial controls and optimizing capital structure. The findings suggest that companies that align financial strategies with long-term goals and apply performance-based planning models are better positioned to ensure profitability and resilience. The article concludes by offering a framework for continuous improvement in financial management, emphasizing innovation, governance, and stakeholder alignment.